Adjusted-Program-Budget Marginal-Analysis for Student Development Activity Planning and Budget Allocation - Maijama’a, Bilkisu; M. Nazri, Engku (International Journal of Engineering and Technology, 2018)
Setting priorities and making decisions on allocation and reallocation of university resources based on the direction of the university as translated in its strategic plan must be executed with transparency and accountability and will be of great importance. It is becoming even more crucial, particularly for universities in Malaysia with the recent budget cut imposed by the Malaysian government. In this paper, we proposed an implementation of Program-Budget Marginal-Analysis (PBMA) which is currently being employed for strategic budget planning in the health industry to be applied for the university strategic budget plan as part of the overall strategic planning process. Firstly, the similarities between the steps in PBMA with the steps involved in planning and executing the university strategic plan were studied. Next, the existing PBMA was adjusted and modeled to suit the needs of the steps involved in selecting and allocating budget for the students of U-ABCâ€™s 2017 development activities. The outcome of this implementation using 0-1 integer programming model showed that the targeted achievements could be realized within the allocated budget that was provided by the university. This adjusted-PBMA will be useful and suitable to be implemented by organizations with key performance indicator-oriented programs and having limited budget allocation issues. Â